The role of expectations in the provision of public goods under the influence of social identity - Matthias Lankau; Marianna Bicskei; Kilian Bizer (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2014)
Individuals who share a common identity show persistently elevated contributions to public goods. Yet, so far the factors that actually trigger this welfare enhancement are not precisely understood. We investigate two channels: (1) subjects' expectations on group members' cooperativeness and (2) the degree to which they reciprocate these expectations by own contributions' i.e. their conditional cooperation. To this purpose we induce identity in the lab and implement an in-group, out-group and partner matching protocol in a ten-period public good game. Our results yield that comparatively higher expectations on in-group than on outgroup members' cooperativeness are the main driver for welfare enhancements in identity homogeneous groups. The degree of conditional cooperation is, however, similar in all matching protocols. Merely individuals initially identified as free-riders seem to reciprocate a limited range of expectations by higher own contributions when matched with in-group than with out-group members. Nevertheless, our findings clearly underline the paramount importance of expectations in determining cooperation under social identity.
Keywords: 330